Idiopathic Orbital Inflammation With Superior Rectus and Levator Complex may be Misdiagnosed as Involutional Ptosis. Issue 4 (June 2020) - Kim, Seungheon; Yang, Sungwon; Park, Jinhwan; Lee, Hwa; Baek, Sehyun
Abstract : Abstract: Idiopathic orbital inflammation (IOI) is a benign inflammatory disease usually confined to the orbit. Two middle-aged patients with IOI have been reported who could have been misdiagnosed as involutional ptosis. Two patients presented to the clinic with eyelid ptosis. One patient's erythrocyte sedimentation rate was slightly increased; the other patient's immunoglobulin G4 (IgG4), IgG, and thyroid-stimulating hormone results were higher than the upper limits of normal. The computed tomographic images and orbit magnetic resonance imaging tests showed an inflammatory condition around the droopy eyelids. They were both admitted to the hospital with diagnosis of IOI, and intravenous antibiotic and steroid treatment were administered, which improved their symptoms.